PERBEDAAN HASIL BELAJAR SISWA YANG HAFAL PERKALIAN DAN YANG TIDAK HAFAL PERKALIAN PADA PENGERJAAN PECAHAN CAMPURAN - Riri Sulistia (Pendidikan Matematika | STKIP YM Bangko, 2020)
This study aims to describe the differences in learning outcomes of students who memorized the multiplication and those who did not memorize the multiplication on the subject of mixed fractions. The hypothesis in this study is that there is a difference between the learning outcomes of students who memorized the multiplication and those who did not memorize the multiplication. This research used experimental research. The population in this study were the fifth grade students of SD N 108 / VI Lubuk Beringin, as samples were the fifth grade students of SD N 116 / VI Muara Siau as the experimental class as many as 23 students and the fifth grade students of SD N 108 / VI Lubuk Beringin as the control class. 23 students. The instrument in data collection uses an essay-shaped test technique. The results of the research data analysis showed that the results of learning mathematics from students who memorized the multiplication were better than the results of learning mathematics for students who did not memorize the multiplication at 95% confidence level. The average learning outcomes and the standard deviation of the two classes being compared were x = 71.94, sdx = 9.74 and y = 60.86, sdy = 8.36. The hypothesis test shows that or 7,1948> 1,721 at the 95% confidence level. Based on the calculations obtained = 7.1948 and = 1.721, then Ha is accepted and Ho is rejected. This proves that the mathematics learning outcomes of students who memorize the multiplication are higher than the mathematics learning outcomes of students who do not memorize the multiplication